Effect of load and speed on the wear behaviour of woven glass fabrics and aramid fibre-reinforced composites - Pihtili, H; Tosun, N (Elsevier Science Sa, 2002)
In the present study, wear behaviour of woven 300 and 500 glass fabrics and aramid fibre-reinforced composite materials are experimentally investigated for 500 and 710 rpm speeds and at two different loads of 500 and 1000 g using a block-on-shaft wear tester. The wear in the experiments was determined as weight loss. The weight losses were measured after different sliding distance conditions. The worn surfaces were also examined by scanning electron microscope (SEM). As a result of this study, it is shown that the applied load on the specimens has more effect on the wear than the speed. Also the weight loss in the woven 500 glass fabric reinforced is more than that in the woven 300 glass fabric-reinforced composite. The weight loss of aramid fibre-reinforced composite is quite low compared with woven glass fabric-reinforced composites. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: wear; aramid; woven glass fabric; composite